"Preaching to the converted": Teaching Calvinistic media ethics in the apartheid era. Issue 1 (2nd January 2017) - de Beer, Arnold S.
ABSTRACT: The purpose of this article is to shed light on a Christian Reformed version of media ethics, more particularly one that was applied for just more than half a century (1960–2014) during the apartheid era and thereafter at the Potchefstroom University for Christian Higher Education (PUCHE), now North-West University (NWU) in South Africa. The contribution of the two main exponents of Christian Reformed media ethics as applied at PUCHE/NWU (and consequently in South Africa), P.G. (Calvyn) Snyman and J.D. (Johannes) Froneman, is discussed. It is argued that their approach to Calvinist media ethics, based on a particular Calvinist interpretation of the Bible, was largely that of pillarisation ( verzuiling ). It is further argued that since the early 1960s, Snyman's Reformed media ethics approach at PUCHE was fundamentally divorced from the external sociopolitical reality of South Africa. Later (shortly before the end of apartheid in 1994), Froneman was well aware of the South African sociopolitical environment, but his version of media ethics mainly remained embedded within a pillarised Christian Reformed research publishing context. The way in which media ethics was taught at the biggest Afrikaans journalism school over a period of five decades, with generations of students entering mainly the Afrikaans media world, is interrogated.